2019
DOI: 10.1111/ecc.13067
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in survivors of adult haematological malignancy

Abstract: Background Survivors of haematological malignancies endure long‐term effects of both treatment and disease. This paper examines factors that influence their quality of life through reporting on the results of a survey. Methods Survey using previously validated quality of life questionnaires for use in cancer management. Participants were adults aged 18 and over who had completed treatment for a haematological malignancy and were between 1 and 5 years post‐treatment. Findings A total of 131 participants, median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
(59 reference statements)
1
11
1
Order By: Relevance
“…1 Cancer pain causes fatigue, loss of appetite, sleep disturbances, mood changes, limitations in daily activities, and problems in one's social life and family relationships. 2 Cancer pain is also associated with depression and anxiety. 3 Kugbey et al showed that depression and anxiety levels decrease, and quality of life increases as a result of a patient's access to health information.…”
Section: Introductionmentioning
confidence: 99%
“…1 Cancer pain causes fatigue, loss of appetite, sleep disturbances, mood changes, limitations in daily activities, and problems in one's social life and family relationships. 2 Cancer pain is also associated with depression and anxiety. 3 Kugbey et al showed that depression and anxiety levels decrease, and quality of life increases as a result of a patient's access to health information.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has assessed only the association between demographic and clinical characteristics and HRQL of patients with hematologic malignancies, showing that patients who are women; employed; lacking in social support; at advanced stages or higher risk; or who are experiencing treatment side effects, anxiety, or depression have higher likelihood of lower HRQL [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Given that chronic pain can have a considerable impact on an individual's physical and psychological function and quality of life (Miladinia, Baraz, Ramezani, & Malehi, ; Inmanuel et al, ), a better understanding of the factors involved in the experience of chronic pain in individuals with cancer would enable the development of better and more specific interventions. Therefore, the aim of this study was to increase our understanding of the physical, cognitive and social factors that are associated with pain interference with activities of daily living in individuals with cancer and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that chronic pain can seriously undermine a person's quality of life as it interferes with daily activities, increases fatigue and loss of appetite, disrupts sleep and mood, and negatively influences social and family relationships (Inmanuel, Hunt, McCarthy, van Teijlingen, & Sheppard ). In addition, chronic pain has been associated with an increased risk of developing psychological disorders such as anxiety and depression (Tomé‐Pires et al, ) and even suicide (Racine et al, ).…”
Section: Introductionmentioning
confidence: 99%